The ball speed and the ball spin created by ground strokes during the rallies in actual tennis match - Kashiwagi, R.; Murakami, S.; Okamura, S.; Takahashi, H. (Science and Racket Sports VI, 2019)
The purpose of this study was to analyse the interaction of ball speed and ball spin of the preceding stroke on both characteristics of the following stroke during a baseline rally of a singles tennis match. Methods: Trackman tennis radar (Trackman Inc.) was used to collect the data. We installed two Trackman tennis radar systems on both side of tennis court and examined the impact of the player`s stroke (speed and spin) on the respective characteristics of the following opponent`s stroke. We analysed 1047 stroke combinations in 699 rallies from five players in three challenger tournament single matches (ATP world rankings ranged from 136 to 200). The obtained data were classified into four types based on the average value of the ball speed and the ball spin; (1): balls with a high speed and a high spin rate, (2): balls with a high speed and a low spin rate, (3): balls with a low speed and a high spin rate and (4): balls with a low speed and a low spin rate. Results: The data analysis shows that if one player`s stroke was (1) or (2), the next return on forehand had a tendency to become (4). Also, in either case of one player`s stroke was (1) to (4), the next return on backhand tended to be average value of the ball speed and the ball spin. We concluded that forehand changes with ball speed of the previous stroke, but backhand does not change with ball speed and ball spin of the previous stroke.